2003
DOI: 10.1029/2003gl017434
|View full text |Cite
|
Sign up to set email alerts
|

Delayed onset of the 2002 Indian monsoon

Abstract: [1] We show that there is a set of dynamical predictors, which facilitate forecasting of a delayed monsoon onset. The main dynamical contributor is the early May propagation of the ''bogus onset Intraseasonal Oscillation'' which triggers a set of events precluding the climatological monsoon onset. We analyze in detail the 2002 monsoon onset and show that it followed a pattern described in our previous study. We notice that the 2003 monsoon onset followed very similar pattern and was delayed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 10 publications
6
44
0
Order By: Relevance
“…On the other hand, Teng and Wang (2003) indicate a much more robust relationship of significant positive relationship with interannual eastern Pacific SST variability for the westward propagating component of the ISO; (2) the intraseasonal ''cloudiness fluctuations'' exhibited longer periods during El Nino years (Yasunari 1980). The character of the monsoon may be influenced via the ENSO-related sensitivity of the northwestward propagating component of the ISO and variations of the boreal summer ISO (Teng and Wang 2003;Flatau et al 2003). But, there is still a need to sort out more clearly the effects from ENSO; and (3) the interannual and intraseasonal fluctuations share a common mode of spatial variability as indicated in Section 2.…”
Section: Intraseasonal Variability (Isv)mentioning
confidence: 99%
“…On the other hand, Teng and Wang (2003) indicate a much more robust relationship of significant positive relationship with interannual eastern Pacific SST variability for the westward propagating component of the ISO; (2) the intraseasonal ''cloudiness fluctuations'' exhibited longer periods during El Nino years (Yasunari 1980). The character of the monsoon may be influenced via the ENSO-related sensitivity of the northwestward propagating component of the ISO and variations of the boreal summer ISO (Teng and Wang 2003;Flatau et al 2003). But, there is still a need to sort out more clearly the effects from ENSO; and (3) the interannual and intraseasonal fluctuations share a common mode of spatial variability as indicated in Section 2.…”
Section: Intraseasonal Variability (Isv)mentioning
confidence: 99%
“…The tendencies of false onset can be noted in zone 4 in northern India and zones 6 and 7 in southern India, where pentad rainfall above 1.5 cm is noted in the first few pentads. This pre-onset rainfall can be attributed to the convection associated with the quadruplet cyclones observed in the Indian Ocean after 9 May 2002 and the subsequent depression over the Bay of Bengal (Flatau et al, 2003). Ignoring this rainfall, the time series of pentad rainfall in 2002 indicates an abrupt and sustained increase in pentad rainfall from about 1.5 cm at around 18 June in zone 1, 15 June in zone 2, 22 June in zone 3, 12 June in zone 4, 9 June in zone 5, 29 May in zone 6 and 6 June in zone 7, indicating onset of the monsoon in different zones.…”
Section: Analysis Of the 10-year Compositementioning
confidence: 99%
“…Compared with IMD data, though the onset times are not degraded in any of the zones, the errors introduced in onset-phase rainfall amount in zones 5 and 7 over NNRP precipitation data suggest the need for improvements in the model setup such as an increase in resolution to resolve the topographic effects. (Flatau et al, 2003;Joseph et al, 2006) showed that it was a false monsoon onset associated with propagating tropical intra-seasonal disturbances/cyclones unrelated to the monsoon onset. In contrast, the monsoon in 2009 was weak, characterized by drought across all of India, and its onset occurred earlier by 1 week (onset on 23 May) (Puranik et al, 2013).…”
Section: Analysis Of the 10-year Compositementioning
confidence: 99%
See 1 more Smart Citation
“…It has been found from an inspection of weekly SST that there were no significant differences in its evolution two monsoons were of similar nature (Flatau et al, 2003). Nevertheless, the July rainfall shows a distinct contrast in the form of a dipole anomaly over India: a 'negative' rainfall anomaly over western India and a 'positive' anomaly over eastern India (Figure 9 (Figure 9(b)), which implies the dominance of these transients during July.…”
Section: Observed and Simulated Mean Rainfallmentioning
confidence: 99%